Risk in the activities of football companies on the example of Olympique Lyonnais and GKS Katowice - Artur Grabowski (Kazimierz Wielki University, 2022)
Purpose: The aim of the paper is to present the economic  situation of two publicly listed companies: GKS Katowice (Poland) and Olympique Lyonnais (France). Both enterprises have different ownership models: Olympique Lyonnnais is a privately owned club, and GKS Katowice belongs to a municipal government. However, both clubs operate in the realities of different market economic system (Poland and France) and also at a different level of economic development. It is common that football companies function under uncertainty and risk. This is heightened by additional characteristic factors for this type of activity such as uncertainty of outcome in sports competition. The adoption of professional sport activities also automatically runs to the risk, but this is not the only problem that the company has to face. In addition, both clubs had to deal with new challenges: COVID-19 pandemic and lockdowns. The paper presented the functioning of both football companies during the COVID-19 pandemic and lockdowns. Methodology: The first part of this research study discusses some particular points of the business strategy and risk management in the context of football companies' management. The economic and financial situation of two football companies is presented, namely: Olympique Lyonnais and GKS Katowice. The focus is on sports, economic and financial criteria to assess the standing of football companies. This paper combines the conclusions from secondary data analysis, content analysis of websites as well as  qualitative and quantitative analysis. The study also employs a comparative analysis. Research and practical limitations: Football companies are in the need to take several actions: a) continuously search for new sources of financing and diversification of activities, b) conclude long sponsorship agreements. Building a solid financial foundation and looking into the future can help football companies get through times of various crises and the COVID-19 pandemic.